INTEGRASI NILAI ISLAM DALAM KURIKULUM NASIONAL UNTUK PENANAMAN ETIKA DIGITAL DAN PENCEGAHAN CYBERBULLYING - Isnaini Prasetiyaningtias; Muhammad Charirul Wafa; Salis Sabila Jadidah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The integration of Islamic values into curriculum development plays a strategic role in addressing the growing crisis of digital morality in educational settings. Despite the increasing emphasis on digital competencies within the national curriculum, current educational practices tend to prioritize technical digital skills while providing limited attention to students’ moral and spiritual development. As a result, conventional preventive approaches that rely primarily on legal regulations and disciplinary measures have proven insufficient in fostering responsible digital behavior. This study aims to develop an alternative curriculum model that integrates technological competence with Islamic moral and spiritual values to strengthen digital ethics among students. The research employs a qualitative library research approach using content analysis of relevant academic journals, books, and educational policy documents. The findings indicate that the integration of Islamic values, particularly those related to faith (aqidah), noble character (akhlaq al-karimah), and ethical principles of Islamic social interaction (muamalah), can provide a comprehensive framework for digital literacy education. Furthermore, the study proposes curriculum integration strategies that embed these values into learning materials, classroom practices, and school culture. The proposed curriculum model contributes to the development of students who are not only digitally competent but also morally responsible and spiritually grounded in navigating the digital environment. Therefore, an integrated curriculum based on Islamic values can serve as a practical reference for creating an ethical, inclusive, and character-oriented digital education ecosystem